2020
DOI: 10.3390/app10144799
|View full text |Cite
|
Sign up to set email alerts
|

High-Precision Cutting Edge Radius Measurement of Single Point Diamond Tools Using an Atomic Force Microscope and a Reverse Cutting Edge Artifact

Abstract: This paper presents a measurement method for high-precision cutting edge radius of single point diamond tools using an atomic force microscope (AFM) and a reverse cutting edge artifact based on the edge reversal method. Reverse cutting edge artifact is fabricated by indenting a diamond tool into a soft metal workpiece with the bisector of the included angle between the tool’s rake face and clearance face perpendicular to the workpiece surface on a newly designed nanoindentation system. An AFM is applied to mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…where R tool_m and R mark_m represent the measured apex radius of the indentation mark and measured cutting edge radius of the diamond tool, respectively. A description of the edge reversal method in detail can be found in the relevant papers [28,33]. As described above, the procedure of evaluating the tip shape of the AFM probe is complex and takes a lot of time in a single measurement.…”
Section: Methods For Evaluating the Geometry Of An Afm Probe Tipmentioning
confidence: 99%
See 2 more Smart Citations
“…where R tool_m and R mark_m represent the measured apex radius of the indentation mark and measured cutting edge radius of the diamond tool, respectively. A description of the edge reversal method in detail can be found in the relevant papers [28,33]. As described above, the procedure of evaluating the tip shape of the AFM probe is complex and takes a lot of time in a single measurement.…”
Section: Methods For Evaluating the Geometry Of An Afm Probe Tipmentioning
confidence: 99%
“…The results obtained by molecular dynamics (MD) simulations indicated that elastic recovery of the indentation mark can be ignored when the indentation depth is greater than 200 nm. The principle of the ultra-precision nanoindentation instrument and the procedure for creating the indentation mark can be found in references [30,33] and will not be repeated in this paper for the sake of brevity.…”
Section: Evaluation Of the Tip Radius Of The Afm Probementioning
confidence: 99%
See 1 more Smart Citation
“…Another in situ measurement system dealing with the on-machine precision form truing of resin-bonded spherical diamond wheels was also proposed [15]. A novel nanotechnology presented a method for measuring the high-precision cutting edge radius of single point diamond tools using an atomic force microscope (AFM) and a reverse cutting edge artifact based on the edge reversal method [16]. For precision measurement of miniature internal structures with high aspect ratios, a spherical scattering electrical field probe (SSEP) was proposed based on charge signal detection.…”
Section: Surface and Profile Measurementmentioning
confidence: 99%
“…The shape of an edge could be measured by optical method or even microscope, which is evaluated by the edge radius. 24 Zhang et al 25 proposed a measurement method for high-precision cutting edge radius of diamond tools by atomic force microscope. Song et al 26 proposed a new method for hard whirling tool edge reconstructing based on fractal interpolation, in which the edge radius is measured and reconstructed in a section.…”
Section: Introductionmentioning
confidence: 99%